2020
DOI: 10.1111/flan.12446
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative writing in mixed classes: What do heritage and second language learners think?

Abstract: This study investigates heritage language (HL) and second language (L2) learners' attitudes and perceptions of their mixed HL–L2 interactions. As part of the activities of a 10‐week course, eight Spanish HL learners and 10 L2 learners worked in mixed dyads to complete a series of collaborative writing tasks designed to leverage their complementary strengths and weaknesses. A beginning‐of‐quarter and an end‐of‐quarter questionnaire were administered. Learners' responses revealed that HL and L2 learners alike ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…Also, students may learn more from actively participating in the assessment process (Berggren, 2019). The benefits of working as assessors and being assessed may outweigh those of solely having works assessed by others (Fernández, 2020). In learner-centered pedagogy, diagnostic assessment can be used by teachers to understand learners and learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, students may learn more from actively participating in the assessment process (Berggren, 2019). The benefits of working as assessors and being assessed may outweigh those of solely having works assessed by others (Fernández, 2020). In learner-centered pedagogy, diagnostic assessment can be used by teachers to understand learners and learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several research studies on learners' perceptions of collaborative writing tasks in language classes have indicated that learners usually believe collaborative writing activities are helpful, with a variety of advantages. These include increasing consciousness and writing skills; enabling good written and verbal communication through a method of concept mapping, realigning linguistic features, getting instant feedback; as well as providing more chances to interact with other classmates, presumably reducing writing anxiety (Fernandez Dobao, 2020). While students have generally positive opinions of collaborative writing, they have voiced certain reservations about participation in collaborative writing activities.…”
Section: Collaborative Writing Beliefsmentioning
confidence: 99%
“…Previous studies have examined grouping strategies in terms of group size (e.g., Fernández Dobao, 2012) and group composition, involving language proficiency (e.g., Leeser, 2004; Watanabe & Swain, 2007) and heritage background (i.e., Fernández Dobao, 2020). Fernández Dobao (2012), in addition to comparing CW and individual writing, examined the effect of group size (i.e., four members vs. pairs) on L2 learners’ collaborative dialogues and writing products.…”
Section: Research Tasksmentioning
confidence: 99%
“…One step further would be to investigate the effect of grouping based on L1 or cultural backgrounds. As a starting point, Fernández Dobao (2020) grouped her Spanish learners based on cultural backgrounds, namely heritage learners (HL)-L2 learners, HL-HL, and L2-L2, and reported that both HL and L2 Spanish learners had very positive perceptions of CW within mixed pairs. Future research can continue to explore the effects of such a cultural grouping (involving heritage and L2 learners) on peer interactions and writing products.…”
Section: Research Tasksmentioning
confidence: 99%